1981
DOI: 10.3109/00498258109045859
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the biotransformation of a 17β-hydroxylated steroid, trenbolone acetate, in rat and cow

Abstract: 1. The metabolism of trenbolone acetate, 17 beta-acetoxyestra-4,9,11-trien-3-one (TBA), an anabolic compound used as a growth promoter, was compared in rat and cow. 2. [6,7-3H] TBA was injected i.v. into rats and a heifer, and bile was collected for 24 h. In both species, the bile was the major route of excretion. TBA undergoes an extensive hydrolysis to 17 beta-hydroxyestra-4,9,11-trien-3-one and the unchanged compound was not detected, but subsequent major metabolic pathways are different in the two species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 25 publications
3
47
1
1
Order By: Relevance
“…TBA is essentially androgenic (Hoffman, 1980). In rats and cows, plasma TBA is deacetylated to trenbolone (Pottier et al 1981), a steroid which has a similar structure to testosterone and has been shown to bind to the rat prostate gland receptor (Raymond et al 1981). Cytosolic receptors for androgenic hormones have been identified in skeletal muscle from rats (Dub6 et al 1976;Snochowski et al 1980), pigs (Snochowski et al 1981 a) and humans (Snochowski et al 198 1 b).…”
Section: Discussionmentioning
confidence: 99%
“…TBA is essentially androgenic (Hoffman, 1980). In rats and cows, plasma TBA is deacetylated to trenbolone (Pottier et al 1981), a steroid which has a similar structure to testosterone and has been shown to bind to the rat prostate gland receptor (Raymond et al 1981). Cytosolic receptors for androgenic hormones have been identified in skeletal muscle from rats (Dub6 et al 1976;Snochowski et al 1980), pigs (Snochowski et al 1981 a) and humans (Snochowski et al 198 1 b).…”
Section: Discussionmentioning
confidence: 99%
“…Estergreen et al (1977) found that 90% to 96% of progesterone can be excreted in feces and 4% to 10% in urine. Pottier et al (1981) observed 80% excretion of injected radio-labeled trenbolone acetate in the bile. Krzeminski et al (1981) found 87% excretion of radio-labeled melengestrol acetate from the liver where 10% to 17% remained unabsorbed and in the parent form.…”
Section: Major Scientific and Environmental Concernsmentioning
confidence: 97%
“…17␤-Hydroxyestra-4,9,11-trien-3-one (trenbolone) is a potent synthetic testosterone analog (67) that does not undergo 5␣-reduction to more potent metabolites (46). As such, trenbolone may induce less growth in prostate and other androgenic tissues that highly express 5␣-reductase.…”
mentioning
confidence: 99%